The encyclopedia of human resource management. Volume two, HR forms and job aids - Lindholm, Jed.; Rothwell, William J., 1951-; Yarrish, Karen K.; Zaballero, Aileen G. (Aileen Guerrero); Wiley InterScience (Online service) (Hoboken : John Wiley & Sons, 2012)
The three volumes in The Encyclopedia of Human Resource Management offer a comprehensive review of the essential issues and most important information available on the topic. Each volume in the encyclopedia contains contributions from some of the most celebrated names in the field of human resource management (HRM) and addresses the myriad challenges faced by today's human resource professionals. Volume 1 puts the focus on the definition of terms and practices that are most relevant to today's human resource management (HRM) professionals. The contributors bring an up-to-date perspective of HRM.
Front Matter -- Recruitment and Staffing. Recruitment and Staffing -- What is Potential? / William J Rothwell -- Recruitment and Staffing Forms -- Talent Management and Development. Talent Management and Development -- What is a High Potential (HiPo)? / William J Rothwell -- Talent Management and Talent Development: What they are, and Why You Should Care / William J Rothwell -- The Different Leadership Styles / Aileen G Zaballero, Jong Gyu Park -- The Difference Between Management Succession Planning and Technical Succession Planning / William J Rothwell -- Career Planning and Development, and Why You Should Care about it / William J Rothwell -- Competency-Based Human Resource Management / William J Rothwell -- Values Modeling, and Why You Should Care about it / William J Rothwell -- Talent Management Forms -- Training and Development Forms -- Work/Performance Analysis and Rewards. Work/Performance Analysis and Rewards -- Performance Appraisals: Understanding, Utilizing, and Unlocking their Potential / Danielle Evanoski -- Work/Performance Analysis Forms -- Rewards Forms -- Employee Relations and Communication. Employee Relations and Communication -- What are Virtual Teams? / Hsin-Ling Tsai -- Employee Engagement, and Why it is Important / Catherine Baumgardner, Jennifer L Myers -- Employee Wellness Programs / Shannon Oyewole, Kelsey Taylor -- What is Disability Competence, and Why Should You Care about it? / Tammy Smith -- What is a b3(BMatureb4 (BWorker? / Dale Bradley Elwood -- Employee Relations Forms -- Measuring Organization Effectiveness. Measuring Organization Effectiveness -- What is HR Transformation? / William J Rothwell -- Organizational Effectiveness, and Why it is Important / Yasser Binsiddiq, Hsin-Ling Tsai -- What is Corporate Culture? / Catherine Baumgardner -- Strategic Planning, and Why You Should Care about it / MJ Zygmont, Daniela A Feenstra -- Why Should You Care about Change Management? / Nai-Fen Su -- Five Approaches to Change in Organizations / William J Rothwell -- Action Research for Sustainable Change / Maria T Kirby -- Accentuating the Positive: Leveraging Strengths to Advantage / William J Rothwell -- How to Identify and Analyze Problems in Your Organization / Bud Benscoter -- What is Six Sigma? / Sohel M Imroz -- Measuring Organization Effectiveness Forms -- Additional Resources. Additional Resources -- The HRIG Model -- Work Forms Chart -- Websites -- Forms Available on the Website for this Volume -- Index.s
Print version record.
Keywords: Personnel management -- Encyclopedias; Personnel management; Business; Personnel management; Electronic books; Encyclopedias